(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
Food organizations recommend an adequate daily intake of unsaturated fatty acids due to their important vital role. Vegetable oils are one of the rich sources in these acids, which have double bonds in their structure, making them vulnerable to oxidation and spoilage when exposed to high temperatures during cooking or storage for a long time. The antioxidant effect of vegetable oils may maintain their nutritional value and stability. The antioxidant effectiveness of oils relates to their chemical composition, quality and quantity of their antioxidant components, in addition to the refining operations carried out on oils before their marketing, which affects their content of these components, resulting in differences in the antioxidant activity between these oils, which in turn leads to their differences on the level of both stability and nutritional value. This research aims to measure the antioxidant activity of some locally available vegetable oils (soybean oil, corn oil, sunflower oil and olive oil) produced by different companies, using the PFRAP method (potassium ferricyanide reducing power), a color spectrophotometric method based on reducing ferric iron (III) ions to ferrous (II) ions and forming a color complex whose absorbance is measured at a wavelength of 700 nm to determine the type of oil and the most effective antioxidant mixture in the laboratory. Samples were collected from the local market in Lattakia, Syria and were measured on consecutive time periods with a time difference (2 months). It was found that the antioxidant activity was different among the different types of vegetable oils and among the companies producing the same type. Also, there was a decrease in the antioxidant effectiveness with the passage of time for all the studied vegetable oils, additionally, it was also found that the antioxidant effectiveness of some oils could be increased by mixing them with other types of oils.